A novel human stem cell‐based biomarker assay for in vitro assessment of developmental toxicity. Issue 19 (14th March 2022) - Jamalpoor, Amer; Hartvelt, Sabine; Dimopoulou, Myrto; Zwetsloot, Tom; Brandsma, Inger; Racz, Peter I.; Osterlund, Torben; Hendriks, Giel
Abstract: Background: Testing for developmental toxicity according to the current regulatory guidelines requires large numbers of animals, making these tests very resource intensive, time‐consuming, and ethically debatable. Over the past decades, several alternative in vitro assays have been developed, but these often suffered from low predictability and the inability to provide a mechanistic understanding of developmental toxicity. Methods: To identify embryotoxic compounds, we developed a human induced pluripotent stem cells (hiPSCs)‐based biomarker assay. The assay is based on the differentiation of hiPSCs into functional cardiomyocytes and hepatocytes. Proper stem cell differentiation is investigated by morphological profiling and assessment of time‐dependent expression patterns of cell‐specific biomarkers. In this system, a decrease in the expression of the biomarker genes and morphology disruption of the differentiated cells following compound treatment indicated teratogenicity. Results: The hiPSCs‐based biomarker assay was validated with 21 well‐established in vivo animal teratogenic and non‐teratogenic compounds during cardiomyocyte and hepatocyte differentiation. The in vivo teratogenic compounds (e.g., thalidomide and valproic acid) markedly disrupted morphology, functionality, and the expression pattern of the biomarker genes in either one or both cell types. Non‐teratogenic chemicals generally had no effect on the morphology of differentiated cells, nor on the expression of the biomarker genes. Compared to the in vivo classification, the assay achieved high accuracy (91%), sensitivity (91%), and specificity (90%). Conclusion: The assay, which we named ReproTracker®, is a state‐of‐the‐art in vitro method that can identify the teratogenicity potential of new pharmaceuticals and chemicals and signify the outcome of in vivo test systems.